Will AI Replace Humans from Human Resources? A Case Analysis - Polisetty, Aruna; Sheela, Paluri (Prabandhan: Indian Journal of Management, 2023)
Purpose : The primary objective of this study was to explore the various factors that impact the integration of artificial intelligence into HR processes, with a specific emphasis on boosting employee engagement. Given the increasing significance of technology adoption within organizations, we aimed to uncover ways in which artificial intelligence can be leveraged to provide enhanced services, ultimately leading to improved organizational success. Methodology : The study employed a hermeneutic phenomenological approach to investigate HR managers’ adoption of technology, particularly AI, in HR management. In-depth interviews were conducted with 15 HR managers from 11 firms in Madhya Pradesh. The study explored how the personality differences of HR managers influenced their intention to adopt AI-based HR practices. The study sought to shed light on the hurdles HR managers face in accepting AI and the unique challenges encountered. Findings : From the study, we found that integrating AI into HR processes enhances efficiency, automates tasks, improves accuracy, and boosts employee engagement. However, drawbacks include employee resistance, privacy concerns, algorithm biases, and the need for human empathy in sensitive issues. HR managers must navigate these challenges while leveraging AI’s benefits for a more efficient and successful organization. Practical Implications : This approach enabled a comprehensive understanding of HR managers’ subjective experiences and perceptions regarding AI adoption while implementing measures to mitigate biases. Originality : In contrast to previous research on the incorporation of AI in HR practices, this case study specifically focused on investigating the challenges associated with integrating AI into HR practices. It aimed to identify these challenges and provide potential solutions to address them effectively.